2017
DOI: 10.1139/bcb-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Oral recombinant human or mouse lactoferrin reducesMycobacterium tuberculosisTDM induced granulomatous lung pathology

Abstract: Trehalose 6'6-dimycolate (TDM) is the most abundant glycolipid on the cell wall of Mycobacterium tuberculosis (MTB). TDM is capable of inducing granulomatous pathology in mouse models that resembles those induced by MTB infection. Using the acute TDM model, this work investigates the effect of recombinant human and mouse lactoferrin to reduce granulomatous pathology. C57BL/6 mice were injected intravenously with TDM at a dose of 25 μg-mouse-1. At day 4 and 6, recombinant human or mouse lactoferrin (1 mg · (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Particularly, it has been observed that mice treated with LF manifest an increase in the proportion of IL-12/IL-10, which results in increased Th1 cells, with a protective role against Mtb ( 100 , 101 ). The anti-inflammatory properties of human and mouse LF were also corroborated in another Mtb mouse infected model ( 102 ). In addition, other studies clearly demonstrated the immunomodulatory role of LF, improving BCG-vaccine efficacy when used as adjuvant ( 147 , 148 ).…”
Section: Human Endogenous Amps Involved In the Fight Against Tb Infecmentioning
confidence: 69%
“…Particularly, it has been observed that mice treated with LF manifest an increase in the proportion of IL-12/IL-10, which results in increased Th1 cells, with a protective role against Mtb ( 100 , 101 ). The anti-inflammatory properties of human and mouse LF were also corroborated in another Mtb mouse infected model ( 102 ). In addition, other studies clearly demonstrated the immunomodulatory role of LF, improving BCG-vaccine efficacy when used as adjuvant ( 147 , 148 ).…”
Section: Human Endogenous Amps Involved In the Fight Against Tb Infecmentioning
confidence: 69%
“…General lung inflammation was assessed as lung weight index (LWI) at 7 days post IV TDM challenge, reflecting peak granulomatous response to TDM 12 [ Figure 1]. As previously reported, TDM-IV Acute treatment increased LWI significantly, at both low (10 μg/mouse) 12 and mid-range (25 μg/mouse) 19 doses, with increased LWI presenting at the higher level. C57BL/6 mice given administered light mineral oil alone (no TDM) did not exhibit changes to LWI (not shown).…”
Section: Comparison Of Tdm Induced Pathology: Hypercoagulation Vs Acumentioning
confidence: 83%
“…Meanwhile, to alleviate symptoms of SARI, we suppose some drugs that are effective in treating TDMinduced pneumonia considering the antigen structure similarity:radix sophorae [34]; lactoferrin [35].…”
Section: Changing Of Expression Profile Of C-type Lecin Family Indicamentioning
confidence: 99%